Complications of Delivery Among Mothers With Spina Bifida - Shepard, Courtney L.; Yan, Phyllis L.; Kielb, Stephanie J.; Wittmann, Daniela A.; Quint, Elisabeth H.; Kraft, Kate H.; Hollingsworth, John M. (Urology (Ridgewood, N.J.), 2019)
To determine rates and types of peripartum morbidity among delivering women with spina bifida (SB) compared to those without SB. The rates of pregnancy and delivery among women with SB have been significantly increasing. Current knowledge of peripartum outcomes for these women is limited. Using 2004-2013 National Inpatient Sample data, we identified all hospitalizations for delivery, distinguishing between women with and without SB. Using a code-based algorithm, we determined whether a complication occurred during the hospitalization. We then fit a series of multivariable logistic models to examine for associations between a complication occurrence during vaginal or cesarean delivery and a woman's SB status. We identified 38,319,814 weighted admissions for delivery, 9516 of which were made by women with SB. Women with SB had a significantly higher rate of cesarean delivery than women without this diagnosis (53% vs 32%, P < .001). The 46.7% of women with SB who delivered vaginally did not have significantly increased odds of a complication associated with their delivery compared to women without SB [odds ratio 1.15, 95% confidence interval 0.99-1.34, P = .066]. However, women with SB who underwent a cesarean delivery did have higher odds of morbidity compared to those without (odds ratio 1.49, 95% confidence interval 1.25-1.78, P < .001). Common complications included preterm delivery, urinary tract infection, hematologic event, and blood transfusion. Compared to women without SB, those with SB deliver more frequently by cesarean section and have higher odds of morbidity associated with cesarean delivery, but not vaginal delivery.